Acceptability of financial incentives for health behaviour change to public health policymakers: a qualitative study - Emma L. Giles; Falko F. Sniehotta; Elaine McColl; Jean Adams (BMC, 2016)
Abstract Background Providing financial incentives contingent on healthy behaviours is one way to encourage healthy behaviours. However, there remains substantial concerns with the acceptability of health promoting financial incentives (HPFI). Previous research has studied acceptability of HPFI to the public, recipients and practitioners. We are not aware of any previous work that has focused particularly on the views of public health policymakers. Our aim was to explore the views of public health policymakers on whether or not HPFI are acceptable; and what, if anything, could be done to maximise acceptability of HPFI. Methods We recruited 21 local, regional and national policymakers working in England via gatekeepers and snowballing. We conducted semi-structured in-depth interviews with participants exploring experiences of, and attitudes towards, HPFI. We analysed data using the Framework approach. Results Public health policymakers working in England acknowledged that HPFI could be a useful behaviour change tool, but were not overwhelmingly supportive of them. In particular, they raised concerns about effectiveness and cost-effectiveness, potential 'gaming', and whether or not HPFI address the underlying causes of unhealthy behaviours. Shopping voucher rewards, of smaller value, targeted at deprived groups were particularly acceptable to policymakers. Participants were particularly concerned about the response of other stakeholders to HPFI - including the public, potential recipients, politicians and the media. Overall, the interviews reflected three tensions. Firstly, a tension between wanting to trust individuals and promote responsibility; and distrust around the potential for 'gaming the system'. Secondly, a tension between participants' own views about HPFI; and their concerns about the possible views of other stakeholders. Thirdly, a tension between participants' personal distaste of HPFI; and their professional view that they could be a valuable behaviour change tool. Conclusions There are aspects of design that influence acceptability of financial incentive interventions to public health policymakers. However, it is not clear that even interventions designed to maximise acceptability would be acceptable enough to be recommended for implementation. Further work may be required to help policymakers understand the potential responses of other stakeholder groups to financial incentive interventions.